Confessing Love to the Nation: Audrey Yu Jia Hui’s Works and Identity Reconstruction - Alberta Natasia Adji; Diah Ariani Arimbi; Adi Setijowati; Nur Wulan; Kukuh Yudha Karnanta (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2018)
This article addressed identity reconstruction through an analysis of two of the most prominent fictional works by one of the Chinese Indonesian young writers, Audrey Yu Jia Hui. In encompassing the idea of identity rewriting, I addressed Hui’s second and third novels respectively, Mellow Yellow Drama (2014) and Mencari Sila Kelima (Searching for the Fifth Principle, 2015), through the post-structural concepts of Derrida’s deconstruction, and also in relation to cultural studies views on identity. The works were analyzed through close-reading technique. The novels were published during the Reformation (Reformasi) era, where politics had served to be a profound aspect that directed the cultural identity and social attitude of the society. In a range of aspects, from narrative structure to their deeper themes, Hui’s literary works were found to draw on a distinguishable set of strategies which enabled Hui to establish her own identity as someone who was liberated, culturally accepted and free to embrace local colors. This article also showed that Audrey Yu Jia Hui’s narratives have served as an acceptance of an individual’s multiple identities, which often depends on the problem at hand as well as the context of choices.